Development of an arithmetic trainer kit for understanding the concepts of Binary Addition and Subtraction - Aminah, Nur; Wirman, Shabri Putra; Fitrya, Neneng (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Digital electronics is the basis of all electronic devices used today. The understanding of digital concepts, especially the concept of arithmetic (binner addition and subtraction) is very important to be applied to more complex electronic systems. The Trainer Kit has been developed as a medium and means of learning and experimenting to understand theoretical concepts for students, college students, and those who just have a hobby in the field of electronics. The stages of making a trainer kit start from system design, hardware design, system testing and implementation of the system. The test results of each arithmetic circuit block show that the system is working properly and can be used by users.